2017
DOI: 10.1080/09286586.2016.1270335
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Age-Related Eye Disease in an Elderly Population

Abstract: Overall, 35.8% of the studied population had at least one of the four diseases. Cataracts, followed by AMD, are the most common age-related eye diseases in the Iranian population, and thus, precise planning along with enhanced diagnostic and therapeutic facilities are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 29 publications
1
17
0
1
Order By: Relevance
“…Over the age of 75, this rate increases significantly to 8.7% and 13.5%. The anomalies characteristic of AMD were found in up to 90% of the examined subjects older than 90 years [3]. In addition, concomitant cardiovascular diseases are often associated with the same risk factors as the development of the abovementioned ocular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Over the age of 75, this rate increases significantly to 8.7% and 13.5%. The anomalies characteristic of AMD were found in up to 90% of the examined subjects older than 90 years [3]. In addition, concomitant cardiovascular diseases are often associated with the same risk factors as the development of the abovementioned ocular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…AMD is an epidemic multi-factorial disease with a prevalence of 8.7% in the world's population, and it has been estimated that by the year 2020, the number of affected people would be about 196 million 22 . According to a report, this figure for Iran is less than the global average (5.8%) 23 . Genome-wide studies have identified multiple genetic loci involved in AMD disease, and these have led to this fact that several important biological pathways, including the complement system, are important in the pathogenesis of the disease 24, 25.…”
Section: Discussionmentioning
confidence: 99%
“…The system was specifically designed for handling by patients and not by health care professionals in order to allow automatic image acquisition in patients' homes or in nursing homes. This need is exacerbated by the mounting pressure to monitor a growing number of patients with chronic eye diseases 26 in an increasingly resource-constrained environment. 27 For example, in the United States, over 100 million people with chronic diseases account for about 75% of health care expenditures.…”
Section: Discussionmentioning
confidence: 99%